Binding studies of lh in benign and malignant uterine tumors - Baghdad Science Journal (مجلة بغداد للعلوم)
the sera levels of luteninizing hormone were investgaited prior tq surgery in 10 postmenopaisal women with benign and 10 postmenopausal women with maliganant healthy